COMPETENCE PROFILE OF AN IDEAL LEADER IN A SELLING CENTER: AN EXPLORATORY ANALYSIS - Schwarzkopf, Rico (PEOPLE: International Journal of Social Sciences, 2020)
Multidisciplinary sales project teams, in the literature also referred to as selling centers, receive increasing attention in both practice and scientific community. In case, selling centers are formed, the sales associate must assume leadership responsibility for the subject matter experts involved. The challenge, however, lies in the sales associate´s lack of formal authority towards these subject matter experts from other departments. This study examined the research question of which competencies sales associates should acquire in order to be accepted as a leader by selling center participants despite their lack of formal authority. For this purpose, twelve selling center participants were interviewed during semi-structured face-to-face interview sessions. The interviewees described the competencies of an ideal leader from a selling center. All interviews were evaluated by applying qualitative content analysis. In addition, a frequency analysis was carried out to evaluate the number of mentions per competence. A total of six competencies were identified which generate acceptance of leadership in selling centers. The conclusion section of this paper deals with a critical appraisal as well as with future research potential.